Analisis Pasar Dari "Kruv Studio" Jasa Kelola Media Sosial Dalam Mengembangkan Bisnis Di Era Digital - Bobby Dewantoro; Moh. Farid Hidayat; Talita Karisma Syaharani; Anggita Dana Salsa Bila; Rheiza Marell Anugerah (Journal of Management and Social Sciences, 2024)
This journal aims to analyze the business market for social media management services and its impact on the growth of MSMEs (Micro, Small and Medium Enterprises). In this digital era, the use of social media has become a key element in marketing strategies, especially for MSMEs who are trying to achieve their targets. This journal conducted an in-depth review of social media management strategies offered by service providers to MSMEs. This research includes market analysis, seeking an in-depth understanding of MSME needs, and evaluating the extent to which social media management services businesses can meet expectations and improve MSME marketing performance. Through interviews, surveys and market data analysis, this journal provides a comprehensive view of market dynamics and the impact of social media management strategies on MSME targets. It is hoped that the results of this research will provide valuable insights for service providers and MSMEs to improve their collaboration in the digital realm, while strengthening the role of social media as an effective tool in supporting the growth of small and medium scale businesses